A critical review of employee turnover model (1938-2009) and development in perspective of performance - WeiBo, Z.; Kaur, S.; Zhi, T. (Academic Journals, 2010)
Retaining employees remains a primary concern for many organizations during days of intellectual property, for intellectual capital has become a critical component of wealth creation. This paper provides a theoretical overview of the different periods of motives and domains or targets of employee retention/turnover and highlights the performing importance from the platform of social capital in research. The objective of this study is to present literature on the complex relationship between individual performance characters and withdraw tendency based on Social Capital Theory. It is generally revealed that in the traditional attitude turnover model the process of employees' volunteer turnover is the reversed transformation process of employees' retention psychology and behaviours, mainly consisting of four sectors (Lee and Mitchell, 1999): first is the quit process caused by job dissatisfaction; then, employees' search for substitutable jobs before turnover; is evaluation on such substitutable jobs; and result is occurrence of turnover behaviour. Finally, an integrative model of the relationship is proposed which argues that performance character may lead to withdraw tendency even turnover behavior through four different routes with the introduction of the Job-Coupling variable. The practical implication of the proposed model for practitioners and researchers encourage further discussion and suggestions.